Distributional Impacts of Taxes and Benefits in Post-Soviet Countries - Fuchs, Alan (World Bank, Washington, DC, 2021)
This study compares the distributional impacts of the main tax and social spending programs in eight countries of the former Soviet Union (Armenia, Belarus, Georgia, Kyrgyzstan, Moldova, the Russian Federation, Tajikistan, and Ukraine) by applying a state-of-the-art fiscal incidence analysis based on the Commitment to Equity methodology. The region is highly interesting due to a unique combination of strong elements of path dependency (socialist legacies) with radical liberalization and welfare state retrenchment. The study examines the actual outcomes in terms of inequality and poverty and assesses the extent to which these outcomes can be attributed to various welfare state policies in these countries. It examines the extent to which taxes and social spending are progressive (whether the average transfer declines with income) and equalizing (whether they reduce inequality). In contrast to the majority of fiscal incidence studies, which are typically limited to the assessment of the impact of direct taxes and transfers, the study estimates the cumulative impact of the tax-benefit system as a whole, including direct and indirect taxes, cash transfers, and transfers in kind such as public education and health care.